Analisis Risiko Produksi dalam Usahatani Jagung dan Strategi Penanganan di Desa Ketro, Kecamatan Karangrayung, Kabupaten Grobogan - Najwa, Syifa Auliya; Yuliawati, Yuliawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to identify sources of production risk in maize farming, analyze their probability and impact, and formulate appropriate handling strategies in Ketro Village, Karangrayung Subdistrict, Grobogan District. The research method used was descriptive-quantitative with a purposive sampling technique of 30 farmers. Data analysis used coefficient of variation (CV), Value at Risk (VaR), and Z-score, as well as risk mapping in four quadrants. Results showed that caterpillar infestation and heavy rainfall were the dominant risks, while plant diseases and drought were the risks with the greatest impact. A CV of 0.20 indicates relatively low risk in aggregate, but a 50% probability of loss indicates the need for mitigation. Strategies implemented by farmers are generally preventive, while mitigative and adaptive strategies are limited. This study recommends risk quadrant-based strategies to improve maize farming resilience.